2009
DOI: 10.1007/978-3-540-92165-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated Vaccines for Pandemic Influenza

Abstract: In this chapter, we will review the development of and clinical experience with the currently licensed seasonal live attenuated influenza vaccines (LAIV) and preclinical studies of H5, H7, and H9 live attenuated pandemic influenza vaccine candidates. Vectored vaccine approaches will not be reviewed in this chapter. Experience with seasonal influenza vaccination has demonstrated the safety and efficacy of LAIV in both children and adults; moreover, cross-protection among antigenically distinct viruses within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…Data from our safety studies showed that both the H3N2 and H1N1 ty/04 att vaccines were attenuated in pigs, as evidenced by the absence of clinical signs of disease upon intranasal vaccination, reduced viral replication in the respiratory tract, and minimal pathological changes in the lungs. The decreased replication of the ty/04 att vaccines in the upper respiratory tracts of pigs is consistent with previous reports showing that the cold-adapted, temperature-sensitive A/Ann Arbor/6/60 influenza vaccines replicate to moderate levels in the nasal cavities of ferrets (13)(14)(15)34) and that NS1-truncated H3N2 influenza vaccines also show limited replication in the nasal cavities in pigs (62). Although the ty/04 att vaccines were detected in BALF samples, the level of viral replication was significantly lower than that of unmodified virus and, more importantly, caused no overt clinical signs and only minimal pathology in the lungs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Data from our safety studies showed that both the H3N2 and H1N1 ty/04 att vaccines were attenuated in pigs, as evidenced by the absence of clinical signs of disease upon intranasal vaccination, reduced viral replication in the respiratory tract, and minimal pathological changes in the lungs. The decreased replication of the ty/04 att vaccines in the upper respiratory tracts of pigs is consistent with previous reports showing that the cold-adapted, temperature-sensitive A/Ann Arbor/6/60 influenza vaccines replicate to moderate levels in the nasal cavities of ferrets (13)(14)(15)34) and that NS1-truncated H3N2 influenza vaccines also show limited replication in the nasal cavities in pigs (62). Although the ty/04 att vaccines were detected in BALF samples, the level of viral replication was significantly lower than that of unmodified virus and, more importantly, caused no overt clinical signs and only minimal pathology in the lungs.…”
Section: Discussionsupporting
confidence: 91%
“…In the United States, a trivalent live attenuated influenza vaccine (FluMist) containing two type A viruses (H1N1 and H3N2) and a type B virus has been licensed for use in humans since 2003 (2,3). Moreover, human LAIVs have been used for many years in Russia without the emergence of new influenza virus reassortants, thus demonstrating the stability of these attenuating phenotypes (2,3,14,38,46). In veterinary medicine, an equine influenza virus LAIV (Flu Avert I.N.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other vaccine platforms, such as LAIV, have been approved and broadly used in humans (34,35) but are not currently licensed for use in swine. Experimental LAIV vaccines have been shown to induce a broadly cross-protective immune response against antigenically different IAV in pigs (19,22,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe the induction of a cross-reactive and broadly protective humoral response by an H7 subtype vaccine candidate in the Newcastle disease virus (NDV) vector, which is well established for use as a bivalent vaccine in poultry against NDV and avian influenza viruses (16,21). Recombinant NDV vaccines for avian influenza virus are approved for use and have been widely distributed in China, primarily for H5 subtype but also for H9 subtype influenza viruses, but poultry are not currently immunized against H7 subtype influenza viruses (22,23).…”
mentioning
confidence: 99%